2017
DOI: 10.18632/oncotarget.21858
|View full text |Cite
|
Sign up to set email alerts
|

Adverse stimulation of 4-nonylphenol in abnormal reproductive organs of female chickens

Abstract: 4-Nonylphenol (4-NP) is a known endocrine disrupting chemical and a persistent environmental contaminant. However, the 4-NP caused mechanism of reproductive toxicity still remains largely unknown in birds. In this study, female chickens (Hy-Line Variety White) were dosed via oral gavage in the early laying period with 0, 50, 100, and 200 mg 4-NP/kg/d for 60 days. Food intake and weight increase were monitored in this organism to investigate chicken growth and development. Moreover, pathological changes of repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Given that GPER and FSHR may cooperate to support follicle selection and maturation during the antral stage ( 41 ), these data suggest that FSHR-mediated intracellular signaling might be perturbed upon disruption of GPER action. Similarly, in chickens, it was demonstrated that 4-Nonylphenol (4-NP) downregulated the ovarian expression of both FSHR and LHR, while it upregulated the levels of steroidogenic enzymes and of the estrogen receptor alpha (erα) ( 81 ). Again, these data may lead to the hypothesis that the disruptive effect of some EDs could be due to the action on FSHR membrane partners, although physical interactions between gonadotropin receptors were never demonstrated in chicken ovaries.…”
Section: Impact Of Eds On Fshr Expression Functioning and Signalingmentioning
confidence: 99%
“…Given that GPER and FSHR may cooperate to support follicle selection and maturation during the antral stage ( 41 ), these data suggest that FSHR-mediated intracellular signaling might be perturbed upon disruption of GPER action. Similarly, in chickens, it was demonstrated that 4-Nonylphenol (4-NP) downregulated the ovarian expression of both FSHR and LHR, while it upregulated the levels of steroidogenic enzymes and of the estrogen receptor alpha (erα) ( 81 ). Again, these data may lead to the hypothesis that the disruptive effect of some EDs could be due to the action on FSHR membrane partners, although physical interactions between gonadotropin receptors were never demonstrated in chicken ovaries.…”
Section: Impact Of Eds On Fshr Expression Functioning and Signalingmentioning
confidence: 99%
“…In terms of sexual differentiation, NP acts as a strong oestrogen agonist and can alter the transcriptional expression of sexual-differentiation genes leading to a change of sex ratio in fish (Sun et al, 2017). Laboratory studies assessing NP toxicity have also demonstrated its ability to cause harm to the endocrine system of divergent species including birds by disrupting normal signalling in the hypothalamic-pituitary-ovarian axis causing developmental abnormalities in ovaries and oviducts (Zhang et al, 2017).…”
Section: Nonylphenol Toxicitymentioning
confidence: 99%